Observing wave propagation of a float serve on a volleyball - Novacek, K. (2011)
There has been research that has determined that the drag forces on a non-spinning volleyball's boundary layer causes the ball to swerve on its trajectory. The purpose of this paper is to develop a numerical model for wave propagation on a volleyball, which we model as a smooth sphere, to show that the waves lead to some turbulence on the ight path of a volleyball. By applying various initial conditions to the three-dimensional wave equation, we can observe waves travelling on its surface. We rst solve the wave equation with spherical coordinates using separation of variables. For our model, we study the wave equation restricted to a sphere and describe it solutions, which are known as spherical harmonics. By using the software Matlab, we are able to implement our equations and initial conditions to observe the wave oscillations on the volleyball.